2019
DOI: 10.1097/md.0000000000018362
|View full text |Cite
|
Sign up to set email alerts
|

Resection might be a meaningful choice for hepatocellular carcinoma with portal vein thrombosis

Abstract: Background: According to the Barcelona Clinic Liver Cancer (BCLC) staging system, the presence of portal vein tumor thrombosis (PVTT) is considered to indicate an advanced stage of hepatocellular carcinoma (HCC) with nearly no cure. Hepatic resection and transarterial chemoembolization (TACE) have recently been recommended for treatment of HCC with PVTT.Methods: We conducted a systematic review to compare the overall survival between patients with HCC and PVTT undergoing hepatectomy, TACE or conservative trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 42 publications
(61 reference statements)
0
22
0
Order By: Relevance
“…However, studies have shown that if the tumor can be completely removed, the patients can benefit from hepatectomy although HCC beyond Milan criteria [22] [23]. If the tumor and PVTT can be completely removed, patients can also obtain longer survival time and higher quality of life [7]. Peng's study showed that the 1-, 3-, 5-year survival rate of PVTT patients in hepatectomy and TACE group were 42.0%, 14.1%, 11.1% and 37.8%, 7.3%, 0.5%, respectively.…”
Section: Hepatectomymentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies have shown that if the tumor can be completely removed, the patients can benefit from hepatectomy although HCC beyond Milan criteria [22] [23]. If the tumor and PVTT can be completely removed, patients can also obtain longer survival time and higher quality of life [7]. Peng's study showed that the 1-, 3-, 5-year survival rate of PVTT patients in hepatectomy and TACE group were 42.0%, 14.1%, 11.1% and 37.8%, 7.3%, 0.5%, respectively.…”
Section: Hepatectomymentioning
confidence: 99%
“…However, approximately 35% -45% of advanced HCC accompanied by portal vein tumor thrombosis (PVTT) [2] [5] [6] which can cause several severe prognosis-related complications such as portal hypertension, upper gastrointestinal hemorrhage and hepatic encephalopathy. A systematic review has shown that the median overall survival (mOS) of advanced HCC patients with PVTT is only about 2.7 months, significantly lower than that of patients without PVTT in which mOS is 24.4 months [7]. According to current guidelines, sorafenib is still recommended as the first-line treatment for HCC with PVTT [2], and this recommendation is based on two phase III clinical trials (SHARP and ORIENTAL)…”
Section: Introductionmentioning
confidence: 99%
“…However, in clinical reality, a high proportion of patients with PVTT are not treated strictly according to the BCLC algorithm but rather undergo individualized therapies, including resection, transarterial chemoembolization (TACE), selective internal radiation therapy (SIRT), or best supportive care (BSC) [11,12]. Moreover, several studies from Asia indicate that well-selected patients might benefit from such alternative therapies [13][14][15]. However, there is no consensus regarding how to identify these patients, and the level of evidence supporting such alternative treatments is low, especially among Western patients.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of treatment modalities and perioperative management, aggressive therapies (including but not limited to liver resection, TACE, and radiofrequency ablation) are no longer contraindications, instead offering alternative treatment options for patients with advanced HCC (11,12). Notably, a growing number of studies have advocated the application of liver resection and TACE in patients with portal vein invasion (13,14).…”
Section: Introductionmentioning
confidence: 99%